Some Examples from the History of the Formation of Eurasian Integration - A., Gonashvili; Mansurovich, Salixov Shoxrux (International Journal on Integrated Education, 2023)
The article presents historical information about the development and formation of Eurasian integration as a regional process in the post-Soviet space. The experience of the transformation of independent states in Eurasia shows that the speed of awareness of the new reality and the adaptation of actors to its requirements in different post-Soviet societies was different from each other. This situation contributes to the idea of the processes of social change taking place in the post-Soviet space as a kind of world laboratory, where different economic, socio-political, cultural and civilizational models are tested, taking into account not only domestic conditions, but also the international context. The problems faced by the states and societies of the Eurasian space are closely intertwined with the fundamental global changes taking place in the world today. The year 2019 marked the 25th anniversary of an important phenomenon in the socio-economic and political life of Eurasian content countries, namely the regional integration process dubbed "Eurasian integration". Eurasian integration is based on the classical integration theory. Integration processes in the post-Soviet space continue to evolve depending on statistical economic indicators. Against this background, the academic community notes the crucial role of science and education in the subsequent evolution of the regional integration process, so the establishment of the Eurasian Science Forum, which takes place in St. Petersburg and contributes to the regional integration process in the post-Soviet space, is a prime example of this.